Settlement of Industrial Relations Disputes Based on Work Decisions Generated by Automatic Systems - Firkha Amidana; Adi Muliawansyah Malie (Greenation Research & Yayasan Global Resarch National, 2026)
The development of information technology encourages the use of automated systems in employment decision-making, such as performance assessment, supervision, sanctions, transfers, and the sustainability of employment relationships. While it improves efficiency, it has the potential to lead to industrial relations disputes, especially if done without transparency, correction mechanisms, and adequate human oversight. This study aims to analyze the legal status of automated system-based work decisions and dispute resolution in Indonesian law, especially in the case of worker mutation to remote locations to encourage resignation and avoid severance pay obligations. The method used is normative legal research with legislative, conceptual, and case approaches. The results of the study show that automated systems are not subject to law, so the responsibility remains with the employer. Decision testing refers to the principles of legal protection, legal certainty, procedural fairness, and accountability.